DRILLING GROUNDWATER FOR RAW WATER IN SEMBIRAN VILLAGE,TEJAKULA DISTRICTS, BULELENG REGENCY - Ketut Agus Karmadi; I Wayan Redana; I Nengah Simpen; Mawiti Infantri; Bambang Soenarto (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2020)
ABSTRACT- Water is an absolute necessity that must be met, both for drinking water and for irrigation. An alternative to meet the water needs other than rainwater or surface water, is by taking underground water by drilling deep wells. Sembiran Village is a village located in Tejakula District, Buleleng Regency, the village is a dry area that requires water, both for drinking water and for agriculture. Location of groundwater drilling including Tejakula groundwater basin. In order to achieve the above objectives, an effective and efficient groundwater drilling technique should be carried out considering that the area geologically has rocks dominated by volcanic lava rock which are the products of Mount Agung and Mount Buyan Beratan Purba. The method of drilling groundwater is carried out in stages starting from drilling a Pilot Hole with a diameter of 6 to 64 meters, followed by an enlargement of 8